Nuevos registros de Proconiini (Hemiptera: Cicadellidae) de la Argentina - Dellapé, Gimena (2013)
Acrogonia citrina Marucci & Cavichioli, Molomea confluens (Melichar), Tretogonia dentalis Emmrich, and Propetes schmidti Melichar are recorded for the first time from Argentina, being the first mention of the genus Propetes Walker in the country. Diagnosis, geographical distribution, and aspects of the biology or phytosanitary importance for each species are provided. In addition, geographical distribution in Argentina of another 16 species of the tribe Proconiini is here included.